1999
DOI: 10.1164/ajrccm.159.3.9804144
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Twelve Southern California Communities with Differing Levels and Types of Air Pollution

Abstract: To study the possible chronic respiratory effects of air pollutants, we designed and initiated a 10-yr prospective study of Southern California public schoolchildren living in 12 communities with different levels and profiles of air pollution. The design of the study, exposure assessment methods, and survey methods and results related to respiratory symptoms and conditions are described in the accompanying paper. Pulmonary function tests were completed on 3,293 subjects. We evaluated cross-sectionally the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
291
2
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 447 publications
(311 citation statements)
references
References 39 publications
(32 reference statements)
11
291
2
7
Order By: Relevance
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 69%
“…Annual means or multiyear means of air pollutants are often used in epidemiologic studies of long -term air pollution effects (Ware et al, 1986;Dockery et al, 1989;Peters et al, 1999a ). In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable.…”
Section: Discussionmentioning
confidence: 99%
“…Model 2 added parental education, which was included in subsequent models so that these results would be adjusted for individual SEP. Model 3 added medical insurance to account for possible diagnostic bias resulting from differential access to care. Model 4 adjusted for a total of 21 covariates that follow the adjustment used by Peters et al in their original CHS study (Peters, Avol, Navidi et al, 1999). Model 5 added census block group population density.…”
Section: Discussionmentioning
confidence: 99%
“…Associations of asthma with housing characteristics, obesity, air pollution, family history and exercise have been previously described (Gauderman, Avol, Lurmann, Kuenzli, Gilliland, Peters et al, 2005;Gilliland, Berhane, Islam, McConnell, Gauderman, Gilliland et al, 2003;Kunzli, McConnell, Bates, Bastain, Hricko, Lurmann et al, 2003;London, James Gauderman, Avol, Rappaport, & Peters, 2001;McConnell, Berhane, Gilliland, Islam, Gauderman, London et al, 2002a;McConnell, Berhane, Gilliland et al, 2002b;McConnell, Berhane, Yao, Jerrett, Lurmann, Gilliland et al, 2006). A detailed description of the selection of communities, subject recruitment, and survey methods to assess demographic, household, activity, and baseline medical characteristics has also been reported (Peters, Avol, Navidi, London, Gauderman, Lurmann et al, 1999). The current analysis is the first examination of the contextual effects of SEP on asthma in the CHS.…”
Section: Study Design and Subjectsmentioning
confidence: 96%
See 1 more Smart Citation